2003
DOI: 10.1002/jnr.10608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deep hypothermia on nitric oxide‐induced cytotoxicity in primary cultures of cortical neurons

Abstract: Nitric oxide (NO) is thought to play a major role during cerebral ischemia. However, the protective efficacy of hypothermia against NO-induced neurotoxicity remains to be examined. In the present study, the degree of neurotoxicity induced by NO was analyzed in two temperature groups (normothermia, 37 degrees C; deep hypothermia, 22 degrees C) of cultured E16 Wistar rat cortical neurons. Two different NO donors, 1-hydroxy-2-oxo-3-(N-ethyl-2-aminoethyl)-3-ethyl-1-triazene (NOC-12) and 1-hydroxy-2-oxo-3-(3-amynop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The neuroprotection in the CNS conferred by hypothermia is attributed to a reduction in the cerebral metabolic rate (CMR), decreased release of neurotransmitters, attenuation of N-methyl-D-aspartate (NMDA) receptor activity, reduction in intracellular calcium influx, decreased lipid peroxidation, and reduced production of reactive oxygen species (ROS). 1 We previously reported that mild (328C) and moderate (278C) hypothermia conferred as much neuroprotection as deep (228C) hypothermia in primary cultured neurones when subjected to long-lasting hypoxia. In addition, profound (178C) hypothermia does not offer any greater protection to the neuronal culture compared with that offered by mild, moderate, or deep hypothermia during hypoxic insults for 24 or 48 h. 2 In contrast to hypothermia, hyperthermia has been shown to increase the vulnerability of certain neurones to infarction.…”
mentioning
confidence: 98%
“…The neuroprotection in the CNS conferred by hypothermia is attributed to a reduction in the cerebral metabolic rate (CMR), decreased release of neurotransmitters, attenuation of N-methyl-D-aspartate (NMDA) receptor activity, reduction in intracellular calcium influx, decreased lipid peroxidation, and reduced production of reactive oxygen species (ROS). 1 We previously reported that mild (328C) and moderate (278C) hypothermia conferred as much neuroprotection as deep (228C) hypothermia in primary cultured neurones when subjected to long-lasting hypoxia. In addition, profound (178C) hypothermia does not offer any greater protection to the neuronal culture compared with that offered by mild, moderate, or deep hypothermia during hypoxic insults for 24 or 48 h. 2 In contrast to hypothermia, hyperthermia has been shown to increase the vulnerability of certain neurones to infarction.…”
mentioning
confidence: 98%
“…The suspension was placed in a poly l-lysine-coated film-bottom dish with a diameter of 35 mm (FD10300; Matsunami Glass Ltd, Osaka, Japan) for calcium imaging or in 2 mm-grid tissue culture dishes (Nunc, Naperville, IL, USA) for cytotoxicity measurements. Grid tissue culture dishes were used to observe the same neurons, as previously described [20,21].…”
Section: Cell Culture and Preconditioningmentioning
confidence: 99%
“…Primary cultures of rat cortical neurons were prepared from 1-day-old newborn rats as described previously [19,20]. The animal were supplied by the Center of Laboratorial Animals in Chinese Academy of Science, Beijing, China.…”
Section: Cell Culturementioning
confidence: 99%